Similarity of ensembles of trajectories of reversible and irreversible growth processes - Klymko, Katherine; Garrahan, Juan P.; Whitelam, Stephen (American Physical Society, 2017)
Models of bacterial growth tend to be “irreversible,” allowing for the number of bacteria in a colony to increase but not to decrease. By contrast, models of molecular self- assembly are usually “reversible,” allowing for the addition and removal of particles to a structure. Suc processes differ in a fundamental way because only reversible processes possess an equilibrium. Here we show at the mean-field level that dynamic trajectories of reversible and irreversible growth processes are similar in that both feel the influence of attractors, at which growth proceeds without limit but the intensive properties of the system are invariant. Attractors of both processes undergo nonequilibrium phase transitions as model parameters are varied, suggesting a unified way of describing typical properties of reversible and irreversible growth. We also establish a connection at the mean-field level between an irreversible model of growth (the magnetic Eden model) and the equilibrium Ising model, supporting the findings made by other authors using numerical simulations.